การพัฒนากระบวนการประสานรายการยาและนำไปปฏิบัติในการติดตามจุดเปลี่ยนในระบบยาผู้ป่วยใน - ฉันทิกา ซื่อตรง (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
Objective: To develop a medication reconciliation process at 3 transition points of care provided for in-patient medication system. The whole proves includes reviewing and maintaining current and accurate medication lists for each individual patient as well as evaluating its outcome by comparing medication error rates found between the study and control group at the interfaces of care. Method: After one month testing period, randomized controlled trial to investigate the medication error rate was conducted at medical and surgical and at emergency medical service wards of Lerdsin Hospital during October 17th, 2005 and February, 21st, 2006. By using cluster random sampling, 234 patients were divided into study and control groups (117 of each). Data were collected at 3 different interfaces of care, during the time of admission, transfer to another unit and discharge. Result: Medication error rates found among patients in the study group were significantly less than those in controls, both at admission and dischanrge. Medication error rates decreased 79.8% from 121.6 per 100 admissions to 24.5 per 100 admissions. Three-fifths (62.7%) of the prescribing orders in study group were found errors at the time of hospital admission and needed to be changed. Mean error rates in the study group was 7.47 per 100 bed day as compared to 21.39 per bed day in the controlled group. Most of the defects bound were due to omission errors, following by wrong dose errors. Conclusion: Medication reconciliation process in inpatient medication system clearly improved medication errors at the interfaces of care.